ITGB4 deficiency induces senescence of airway epithelial cells through p53 activation. (15th February 2019) - Yuan, Lin; Du, Xizi; Tang, Sha; Wu, Shuangyan; Wang, Leyuan; Xiang, Yang; Qu, Xiangping; Liu, Huijun; Qin, Xiaoqun; Liu, Chi
Abstract : Aging is characterized by a progressive loss of physiological integrity, leading to impaired organ function and, ultimately, increased vulnerability to death. Many complex diseases are related to aging, including asthma. In the lung, the airway epithelium serves as the first barrier to prevent the access of inspired external stimuli and dictates the initial stress responses. Notably, in the airway mucosa of asthma patients, an increase in senescent airway epithelial cells has been detected. Although it has been speculated that the senescence of airway epithelial cells could increase asthma susceptibility and aggravate asthma severity, the role of cell senescence in the development of asthma remains unclear. Integrin β4 (ITGB4) is a structural adhesion molecule with complex physiological functions that is downregulated in airway epithelial cells of asthma patients. This study demonstrates that the expression of ITGB4 in airway epithelial cells is downregulated significantly under oxidative stress or upon inflammatory stimulation. Moreover, we show that ITGB4 deficiency induces the senescence of airway epithelial cells through the activation of the p53 pathway both in vitro and in vivo . Together, our results demonstrate that airway epithelial senescence induced by ITGB4 deficiency after oxidative stress or inflammatory stimulation may be involved in the pathogenesis of asthma. Understanding the contribution of ITGB4 deficiency to the senescence of airway epithelial cells in asthma patients may provide new therapeutic approaches for the treatment of asthma. Abstract : Aging is related to many diseases including asthma. Senescence of airway epithelial cells is increased in asthma patients. Here, it is demonstrated that ITGB4 expression in airway epithelia is downregulated under oxidative stress or inflammation stimulation. ITGB4 deficiency induces the senescence of airway epithelia by activating the p53 pathway. These results indicate that oxidative stress or inflammatory stimuli may contribute to the senescence of airway epithelia and could contribute to the pathogenesis of asthma.